Is there a difference in ischaemic heart disease deaths that occur without a preceding hospital admission in people who live in rural compared with urban areas of Aotearoa New Zealand? An observational study - Miller, Rory; Turner, Robin; Davie, Gabrielle; Stokes, Tim; Crengle, Sue; Mcleod, Alex; Tane, Taria; Nixon, Garry (BMJ open, 2025)
ObjectivesUnlike comparable countries, acute coronary syndrome (ACS) mortality is similar among patients who present to rural and urban hospitals in Aotearoa New Zealand (NZ). The aim of this study was to determine whether differences in ischaemic heart disease (IHD) deaths that occurred without a preceding hospital admission in rural and urban populations explained this finding.DesignRetrospective observational study using the National Mortality Collection (MORT) and National Minimum Dataset (NMDS) for hospital discharges datasets.SettingPeople in NZ who died from IHD were categorised based on their rural–urban status (U1 (major urban), U2 (large urban) and rural) using the Geographic Classification for Health and prioritised ethnicity (Māori—NZ’s Indigenous population and non-Māori).ParticipantsAll people 20+ years who died from IHD between July 2011 and December 2018.Primary and secondary outcomesThe outcome was the lack of a hospital admission preceding IHD death, identified by linking the NMDS with MORT. This was measured for the 30 days and 1 year prior to death and for all-cause and IHD hospitalisations separately.ResultsOf the 37 296 deaths, a similar percentage of rural and urban residents died without an all-cause (rural 63.2%, U2 60.8%, U1 62.8%) or IHD (rural 70.9%, U2 69.0%, U1 70.1%) admission in the preceding 30 days, or without an all-cause (rural 32.8%, U2 35.5%, U1 35.5%) or IHD (rural 52.7%, U2 52.6%, U1 51.9%) admission in the preceding year. Exceptions were deaths that occurred without a prior admission for rural non-Māori aged 55–64 (higher odds) and 75+ years (lower odds) compared with U1 non-Māori 55–64 and 75+ years, respectively, across all four outcome measures.ConclusionsThis study suggests that the lack of difference in ACS mortality for patients who present to NZ rural and urban hospitals is not explained by IHD death that occurred without a recent preceding hospital admission.